Pembuatan Mono-Diasilgliserol Dengan Reaksi Gliserolisis Menggunakan Katalis Enzim Lipase - Nur Asma Deli; Antonius Jumadi Sihotang (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2024)
CPO and its main product, namely RBD Palm Olein, are commodities that have strategic value to be developed by processing them into derivative products to increase selling value.One product that is widely used and needed by the market today that can be processed from palm oil is Mono-Diacylglycerol (MDAG) emulsifier.This study aims to determine the process of making Mono- Diacylglycerol (MDAG) by glycerolysis reaction using a lipase enzyme catalyst and to determine the best enzyme catalyst concentration.based on the characteristics and quality test of the resulting MDAG products. The stages carried out in this study began with the characterization of raw materials, the synthesis of Mono-Diacylglycerol (MDAG), product purification from catalysts, adsorbents and solvents, and tested the characteristics and quality of the products produced. In this study, the best enzyme catalyst concentration was found in the use of 6% catalyst with MDAG acquisition of 59.8%, ALB content of 0.2%, pH value at number 6, density of 0.95 gr/cm3, surface tension of 18 .65dynes/cm. And the results of the functional group test using FTIR on the resulting MDAG show thatthe functional groups contained in MDAG, namely 3R-COOR'-2OH and 3R-2COOR'-2OH were read on infrared absorption from FTIR at a wavelength of 721.38 cm-1 – 3392.79 cm-1.